"If not me, who?": Awareness- and Self-Advocacy-Related Experiences of Adults With Diverse Rare Disorders. (January 2023) - Plackowski, Emily F.; Bogart, Kathleen R.
In a two-study project, researchers used qualitative methods and inductive thematic analyses to investigate the lived awareness- and advocacy-related experiences of 27 adults with over 35 different rare diseases, disorders, or disabilities (RDs). In Study 1, participants in two focus groups described how a lack of RD awareness led to experiences with several types of stigma, complicated their expressions and disclosures of disability, and spurred them to work towards awareness. Participant priorities identified in Study 1 motivated researchers to design and conduct Study 2. In Study 2, researchers interviewed 18 RD self-advocates about their lived experiences with and ideas regarding advocacy. Their recommendations included increasing social and systemic support, education, and media and professional representation. Advocates in Study 2 also warned of potential roadblocks to self-advocacy and change, including systemic invalidation and bias, lack of access to activist spaces, and limited time and energy for advocacy. Overall, analyses exposed the complex and interwoven influences of RD awareness and advocacy.